Digital Transformation and Operational Productivity of Maritime Transport Enterprises: Evidence from Global and Indonesian Contexts - Samekto, Agus Aji (LPPM of NAROTAMA UNIVERSITY, 2025)
This study examines the influence of digital transformation on the operational productivity of maritime transport enterprises, integrating both global evidence and Indonesian maritime sector data. Using panel data from 58 maritime companies over 2018–2024, we apply quantitative regression analyses to assess the elasticity between digital integration and key operational outcomes, including fuel efficiency, voyage duration, and port turnaround time. The results indicate a significant positive elasticity of 0.42 between digitalization indices—encompassing blockchain-based logistics, artificial intelligence-assisted scheduling, and smart gate systems—and productivity growth. Firms adopting advanced digital tools demonstrate a 15–22 percent improvement in energy cost efficiency and a 10–14 percent reduction in carbon emissions, corroborating literature on maritime decarbonization, green supply chains, and smart port operations. Moreover, mediation analyses reveal that digital maturity significantly enhances the effectiveness of fuel management and scheduling systems, while robust governance and risk management frameworks amplify these effects. These findings provide actionable insights for policymakers and maritime managers seeking to enhance sustainable operational performance through structured digital adoption.